Legality of MSMEs for Tourism Village Development - S, Ali; Fitria, Nyimas; Kartika Meilani, Indah; Sutrisno, Endang; Indraswari, Sri Primawati (Jurnal Sosial Teknologi, 2024)
This research explores the implementation of legalities faced by Micro, Small and Medium Enterprises (MSMEs) in tourist villages, with a focus on understanding and compliance with applicable regulations. The research method involves in-depth interviews with MSME owners and related stakeholders in the tourist villages selected for the survey. The research results identified that MSMEs in tourist villages often face difficulties in understanding and fulfilling the necessary legal requirements, such as business permits. These findings highlight the need for a more integrated approach and active assistance from relevant parties, including government and non-government organizations, to increase MSMEs' understanding and compliance with applicable regulations. The results show that the legality of MSMEs, such as business permits and product certificates, has a significant impact on the growth and sustainability of tourist villages. Implementing clear regulations and a good understanding of the legal process can increase the competitiveness of MSMEs and strengthen the local economy. This research provides policy recommendations for the government and practical guidelines for MSME owners in utilizing legality to support sustainable development of tourist villages.